Implementation of the family planning program in selected Barangays of Luzviminda Health Center - Daliposa, Virginia T. (Manila : National University, 2008)
The study would enlighten the real importance of family planning program to their family life. Awareness on the family planning program will help them determine the proper spacing of the childbirth and proper rearing of children based on the manageable income of the family. Thus the respondents would be able to maintain their reproductive health.
Title page -- Approval Sheet -- Acknowledgement -- Abstract -- Conclusion -- Recommendation -- Table of contents -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Questionnaire -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.